ANALISA KEKUATAN KOLOM GEDUNG RUMAH SAKIT TYPE C MEDAN LABUHAN PADA WILAYAH ZONA GEMPA YANG BERBEDA (STUDI KASUS) - Rahman, Rizki; Sutrisno, Sutrisno (Jurnal Riset Rekayasa Sipil, 2021)
Indonesia is a country that is a often hit by disasters, this is due to the meeting of 4 tectonic plates of the earth. The city of Padang is right at the meeting between the Indo-Australian plate and Eurasia so that it puts the city of Padang as one of the cities prone to earthquakes. This research analyzes the type C hospital building that was originally designed in the Medan city location to be designed in Padang city with the aim to determine the strength of the structure and the need for the width of the column reinforcement in the building. The first step is to determine the spectral response value of the Padang region earthquake, a short period of 0.2 seconds Ss = 1,289 g and a period of 1 second S1 = 0.549 g. Second is calculating dead load, live load and static earthquake load equivalent to SNI 03-1726-2012 and force output in using ETABS software, and third is calculating the column reinforcement area requirements. The results of the analysis show that the width of the column reinforcement there is a difference = 4750.00 mm against field data = 6801.24 mm in the dimensions of the column 500 mm x 500 mm with a value of = 2051.24 mm and an increase in the value of the calculation reinforcement area in the 700 mm column x 700 mm is = 9800.00 mm from the field data = 9068.32 mm with a selection = 731.68 mm.